Investigating significant learning of geometry in 8th grade with the support of a didactic sequence - Perla Christina Nunes da Silva; Lilian Nasser (Universidade Federal do Oeste da Bahia, 2021)
This article is part of a master dissertation, investigating the efficiency of a didactic sequence of Geometry, applied to 8th year students, concerning the concept and properties of triangles. The research was based on the Van Hiele Theory to determine the level of learning before and after the application of the didactic sequence, in parallel to the traditional teaching of Geometry. The didactic sequence was elaborated in order to induce the understanding of the properties of triangles and their generalization, reaching a Significant Learning, according to the theories of Ausubel and Skemp. The activities of the didactic sequence were different from the instructional text for the use of concrete materials and the constant demand for arguments and justifications. After some time it was possible to verify the retention of the learning, allowing the conclusion that the students had reached a significant learning, according to the answers to a pot-test.